2021
DOI: 10.1177/2377960821993515
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Isometric Exercise and Counseling on Level of Pain Among Patients With Knee Osteoarthritis

Abstract: Introduction Osteoarthritis (OA) is one of the emerging health issues in Asian countries in elderly population. Knee osteoarthritis (KOA) is a major age related public health issue characterized by progressive loss of articular cartilage resulting in pain, functional impairment, disability and diminished quality of life. The aim of this study was to assess the effectiveness of Isometric exercise and counseling on level of pain among patients with KOA. Methods Quantitative research approach and a quasi-experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Azukizawa et al [ 20 ], Centeno et al [ 24 ], Mikesky et al [ 36 ], and Multanen et al [ 37 ] generally detected no significant changing after physical exercise related to pain and functional outcomes. Dinçer et al [ 25 ], Ikuta et al [ 31 ], Kangeswari et al [ 32 ], Knoop et al [ 35 ], and Vassao et al [ 41 ] detected better results after a physical exercise treatment both for the pain scale and functional outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Azukizawa et al [ 20 ], Centeno et al [ 24 ], Mikesky et al [ 36 ], and Multanen et al [ 37 ] generally detected no significant changing after physical exercise related to pain and functional outcomes. Dinçer et al [ 25 ], Ikuta et al [ 31 ], Kangeswari et al [ 32 ], Knoop et al [ 35 ], and Vassao et al [ 41 ] detected better results after a physical exercise treatment both for the pain scale and functional outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Specific muscle strengthening interventions [ 25 , 28 , 31 , 35 , 36 , 41 ] and isometric exercises are proposed [ 32 ]. One of the intervention proposals is individually progressed and consisted of 5 min warm-up and hopping (3–5 sets, 15 s of rest between sets) exercises of approximately 3–4 min [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isometric exercise plays an important role in physiotherapeutic practice as part of rehabilitation from many different injuries. This is exemplified none more so with the knee, with isometrics being prescribed for the rehabilitation of osteoarthritis of the knee [7][8][9][10][11][12][13][14][15]. Interest in isometric training spiked after Rio et al [7] reported significantly greater pain relief following a single session of isometric exercise as compared with isotonic exercise.…”
Section: Introductionmentioning
confidence: 99%
“…PA is considered an important, modifiable lifestyle behavior that can reduce pain and improve mobility in people with KOA [7][8][9]. Numerous arthritis guidelines and studies specifically report that people with KOA can benefit from improved symptoms and maintain health from moderate PA [10][11][12]. As the fourth leading cause of death worldwide, physical inactivity can increase the risk of noncommunicable diseases, such as cardiovascular or metabolic disorders [2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%